Comparison of autoinflammation and autoimmunity using TRAPS and rheumatoid arthritis as prototypes of these conditions. (December 2009) - Aziz, Azad; Wong, Chi H; Emery, Paul; McDermott, Michael F
Classical autoimmune diseases are associated with the presence of autoantibodies and autoantigen-specific T cells. However, in addition to the classical major histocompatibility complex class II-associated diseases, such as systemic lupus erythematosus and rheumatoid arthritis, the autoimmunity paradigm has also been the dominant conceptual framework when considering the pathogenesis of a range of other chronic inflammatory conditions, such as inflammatory bowel disease (ulcerative colitis and Crohn''s disease) and systemic juvenile idiopathic arthritis. Several difficulties arise when the autoimmunity concept is invoked to describe the self-directed tissue inflammation encountered in many diseases, such as ankylosing spondylitis, inflammatory bowel disease and psoriasis; these include an absence of autoantibody associations, which is seen in all these conditions, and a lack of major histocompatibility complex allelic associations. These autoinflammatory diseases are not associated with the presence of autoantibodies and autoantigen-specific T cells, and appear to be mainly cytokine driven. For the purpose of this review, we have chosen to describe the autosomal dominant, TNF receptor-associated periodic syndrome as a prototype of this category of disorders. We compare the genetic basis, pathophysiology and treatment of TNF receptor-associated periodic syndrome with rheumatoid arthritis, which we present as an example of an autoimmune disease.